Parallel transjugular intrahepatic portosystemic shunt for controlling portal hypertension complications in cirrhotic patients - He, Fu-Liang (Baishideng Publishing Group Inc, 2014)
AIM: To evaluate the feasibility of a second parallel transjugular intrahepatic portosystemic shunt (TIPS) to reduce portal venous pressure and control complications of portal hypertension. METHODS: From January 2011 to December 2012, 10 cirrhotic patients were treated for complications of portal hypertension. The demographic data, operative data, postoperative recovery data, hemodynamic data, and complications were analyzed. RESULTS: Ten patients underwent a primary and parallel TIPS. Technical success rate was 100% with no technical complications. The mean duration of the first operation was 89.20 ± 29.46 min and the second operation was 57.0 ± 12.99 min. The mean portal system pressure decreased from 54.80 ± 4.16 mmHg to 39.0 ± 3.20 mmHg after the primary TIPS and from 44.40 ± 3.95 mmHg to 26.10 ± 4.07 mmHg after the parallel TIPS creation. The mean portosystemic pressure gradient decreased from 43.80 ± 6.18 mmHg to 31.90 ± 2.85 mmHg after the primary TIPS and from 35.60 ± 2.72 mmHg to 15.30 ± 3.27 mmHg after the parallel TIPS creation. Clinical improvement was seen in all patients after the parallel TIPS creation. One patient suffered from transient grade I hepatic encephalopathy (HE) after the primary TIPS and four patients experienced transient grade I-II after the parallel TIPS procedure. Mean hospital stay after the first and second operations were 15.0 ± 3.71 d and 16.90 ± 5.11 d (P = 0.014), respectively. After a mean 14.0 ± 3.13 mo follow-up, ascites and bleeding were well controlled and no stenosis of the stents was found. CONCLUSION: Parallel TIPS is an effective approach for controlling portal hypertension complications.